Justicia gendarussa (BURM F.) (WILLOW-LEAVED Justicia) from Peninsular Malaysia: leaf anatomy and micromorphology - Aidatul Aifa Mohd Tajudin,; Che Nurul Aini Che Amri,; Rozilawati Shahari, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Acanthaceae or the Acanthus family has been commonly used by local peoples as traditional medicines, especially in Peninsular Malaysia. Justicia gendarussa, also known as ‘daun rusa’ or ‘genda rusa,’ treats inflammatory disorders, asthma, hepatic injuries, arthritis, and digestion problems. Many taxonomists nowadays struggle to identify Acanthaceae species due to morphological similarities and incomplete parts during the identification process. Other than that, there has been no comprehensive study of Justicia gendarussa leaf anatomy to date. Therefore, this study aims to describe the leaf’s anatomical and micromorphological characteristics that would be useful to identify this plant species. The leaf anatomical study involved several methods such as cross-section using a sliding microtome and observation under a light microscope. While the leaf micromorphology method involved the observation under a scanning electron microscope (SEM) of the epidermis of abaxial and adaxial surfaces. The result of this study showed the presence of collenchyma, sclerenchyma, and mucilage cells in the petiole and midrib. The patterns of petiole and midrib vascular bundles were described as the main vascular bundle (opened system with continuous rings of the vascular bundle) with two additional vascular bundles located the above right and left of the main vascular bundle near each wing. The cystolith cells are present in the epidermis and parenchyma cortex while glandular and non-glandular trichomes were recorded in the species studied. In conclusion, comprehensive data for the leaf anatomical and micromorphological characteristics can be used to supplement data in the identification of Justicia gendarussa.